Zasady dynamiki misyjnej według św. Pawła (refleksja misjonarza) - KROEGER, JAMES H. (Annales Missiologici Posnanienses, 2010)
Saint Paul, apostle par excellence, tirelessly labored to spread the Gospel, particularly in the Gentile world. His missionary travels and encounter with diverse peoples, cultures, and religions form the matrix or context of his missionary methods. A comprehensive examination of Paul’s writings yields much mission wisdom and insight shaped by his apostolic experience and dynamic faith. This presentation suggests ten “mission principles”-derived from Paul’s profound reflection and “applied” to missionary engagement today.